Results on Difference-Differential Polynomial of Entire Functions - Lowha, Tapas (Sarajevo Journal of Mathematics, 2024)
In this paper, we deal with the uniqueness results of derivatives of difference-differential polynomials of entire functions sharing a value with CM(IM). The results of this paper extend the results of K. Liu, X.L. Liu and T.B. Cao[8,9] and K. Zhang and H. Yi[17] and many others.